2010
DOI: 10.1093/rpd/ncq556
|View full text |Cite
|
Sign up to set email alerts
|

Active personal dosemeters in interventional radiology: tests in laboratory conditions and in hospitals

Abstract: The work package 3 of the ORAMED project, Collaborative Project (2008-11) supported by the European Commission within its seventh Framework Programme, is focused on the optimisation of the use of active personal dosemeters (APDs) in interventional radiology and cardiology (IR/IC). Indeed, a lack of appropriate APD devices is identified for these specific fields. Few devices can detect low-energy X rays (20-100 keV), and none of them are specifically designed for working in pulsed radiation fields. The work pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 4 publications
0
19
0
2
Order By: Relevance
“…Folglich zeigen diese Dosimeter eher eine Ortsdosis. Zudem hat eine Studie gezeigt, dass diese Dosimeter für den Einsatz unter gepulster Röntgenstrahlung nur limitiert einsetzbar sind [10].…”
Section: Diskussionunclassified
See 1 more Smart Citation
“…Folglich zeigen diese Dosimeter eher eine Ortsdosis. Zudem hat eine Studie gezeigt, dass diese Dosimeter für den Einsatz unter gepulster Röntgenstrahlung nur limitiert einsetzbar sind [10].…”
Section: Diskussionunclassified
“…Dies entspricht etwa der natürlichen Strahlenbelastung der Bevölkerung in Deutschland. Wie bei Studien mit ähnlichen EZD[10] ist davon auszugehen, dass die tatsächliche Dosis auch bei den vom RaySafe-EZD ermittelten Werten, höher liegt. Im OP-Team bekommt der Operateur die höchste Exposition, trotzdem ist diese verhältnismäßig niedrig.…”
unclassified
“…The final results of the simulations of Koukorava et al [49] indicate that for overcouch irradiation the eyes and the hands are about six times more exposed compared with the case where the tube is below the operating table and that for the lateral left anterior oblique projection, placing the ceiling-suspended shield at the left side of the operator is twice as effective for protection of the eyes compared with the case where it is placed above the patient. Clairand et al [50,51] evaluated several active personal dosimeters for interventional radiology in laboratory conditions and in hospitals, raising the difficulties of measuring in pulsed radiation fields. Domienik et al [52] reported results obtained in interventional cardiology and interventional radiology facilities in 34 European hospitals.…”
Section: Occupational and Lens Dose Evaluationmentioning
confidence: 99%
“…On the other hand, active personal dosimeters (APDs) that often provide realtime readings, may introduce substantial errors when used in fluoroscopy. Most of the currently commercially available APDs may not have appropriate characteristics for use in pulsed X-ray fields, such as those observed in EVAR, due to the dependence of their response on dose rate, X-ray pulse frequency and duration, as well as on angle of incidence (Clairand, et al, 2011). For example, APDs of the type used by surgeons that carried out EVAR (Panuccio, et al, 2011) were found to have substantial energy dependent response, that varies up to a factor of two in the spectral region of interest and saturates at dose rates above 30 mGy/min.…”
Section: Assessment Of Staff Radiological Riskmentioning
confidence: 99%